2014
DOI: 10.1016/j.colsurfb.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface properties on Escherichia coli adhesion are modulated by shear stress

Abstract: The adhesion of Escherichia coli to glass and polydimethylsiloxane (PDMS) at different flow rates (between 1 and 10 ml.s -1 ) was monitored in a parallel plate flow chamber in order to understand the effect of surface properties and hydrodynamic conditions on adhesion. Computational fluid dynamics was used to assess the applicability of this flow chamber in the simulation of the hydrodynamics of relevant biomedical systems. Wall shear stresses between 0.005 and 0.07 Pa were obtained and these are similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 50 publications
1
65
0
Order By: Relevance
“…Thus, it seems natural that surface roughness was not controlling bacterial adhesion. In a previous work using this strain, it was verified that shear stress can affect cell adhesion and can even modulate the effects of the surface properties (Moreira et al, 2014a). Thus, it is also possible that the hydrodynamic conditions were controlling bacterial adhesion in the present study and that this effect was more significant than other factors such as bacterial composition, bacterial concentration, medium composition or surface properties.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, it seems natural that surface roughness was not controlling bacterial adhesion. In a previous work using this strain, it was verified that shear stress can affect cell adhesion and can even modulate the effects of the surface properties (Moreira et al, 2014a). Thus, it is also possible that the hydrodynamic conditions were controlling bacterial adhesion in the present study and that this effect was more significant than other factors such as bacterial composition, bacterial concentration, medium composition or surface properties.…”
Section: Discussionmentioning
confidence: 55%
“…Escherichia coli JM109(DE3) from Promega (USA) was used in this study because it has shown a good biofilm forming ability in a variety of in vitro platforms operated at different shear stresses 2014a;Teodósio et al, 2012). Additionally, it was shown that its biofilm formation is similar to other E. coli strains which are often used for antimicrobial susceptibility and disinfection tests (Gomes et al, 2014).…”
Section: Bacterial and Culture Conditionsmentioning
confidence: 99%
“…In this work, this tendency was observed on average for 83% of the obtained results. In a previous study, E. coli adhesion to an hydrophilic glass and to an hydrophobic polymer at different shear stresses (between 0.005 and 0.07 Pa) was evaluated (Moreira et al, 2014b). Those results have shown that the effect of surface properties is modulated by shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…Cell adhesion and subsequent biofilm formation can be postively or negatively affected by shear stress since it is correlated with the fluid velocity and consequently with mass transfer (Moreira et al, 2014a). During the adhesion and maturation phases, a higher fluid velocity will increase the transport of nutrients and cells which has a postive effect on cell adhesion and biofilm formation (Moreira et al, 2014a;2014b). However, a higher shear stress may prevent cell attachment or promote cell detachment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation